The role of public awareness campaigns in sustainable development - Anna Borawska (Economic and Environmental Studies (E&ES), 2017)
The concept of sustainable development has been present in political discourse for many years. Striving to achieve it has become a worldwide priority. Success in this field depends not only on the right government policies. It is also a matter of society engagement. There are different direct and indirect tools intended to promote and reinforce positive changes in social attitudes. Among the most important ones are public awareness campaigns. The aim of the article is to present the ways in which they can contribute to sustainable development and how their positive impact should be properly assessed.
Keywords: Q5; M31; 330; sustainable development; public awareness campaigns; social marketing